Reflective Functioning in Children and Adolescents With and Without an Anxiety Disorder - Chevalier, Valérie; Simard, Valérie; Achim, Julie; Burmester, Pamela; Beaulieu-Tremblay, Thalie (Frontiers in Psychology, 2021)
Reflective functioning (RF), meaning the capacity to interpret mental states (intentions, emotions, thoughts, desires, beliefs) underlying one’s own and others’ behaviors, may help understand the dysfunctional self-regulation associated with anxiety disorders. However, research on anxiety and RF in clinical samples is scarce. This study aimed to assess whether mothers’ and youths’ RF were associated with youths’ (a) anxiety disorders and symptoms and (b) internalizing symptoms. Another goal was to explore whether RF predicted anxiety and internalizing symptoms beyond the more commonly established effect of attachment. Canadian children and adolescents aged between 8 and 16 years and their mothers were recruited in an outpatient psychiatric clinic (clinical group with a diagnosed anxiety disorder, n = 30, mean age = 11.5 ± 2.8 years) and in the general population (non-clinical group, n = 23, mean age = 11.5 ± 2.1 years). The Child Attachment Interview was used to assess youths’ attachment along with three dimensions of RF (global, regarding self, regarding others). Mothers’ attachment and RF were assessed with the Adult Attachment Interview. Children’s and adolescents’ anxiety and internalizing symptoms were measured with the Behavior Assessment Scale for Children, second version. The clinical and non-clinical groups did not differ in mothers’ or youths’ RF. However, in the overall sample, youths’ RF regarding themselves and maternal attachment preoccupation were associated with internalizing symptoms. Sequential regression analyses revealed that higher RF regarding self predicted a higher level of self-reported internalizing symptoms, beyond the effect of maternal attachment (β = .43, p < .05). This study’s findings suggest that clinically anxious children and adolescents have adequate RF. We propose that the sustained hypervigilance and apprehension associated with anxiety make anxious youths sensitive to their own and others’ mental states. Our findings suggest that psychotherapeutic treatments for anxiety should make use of patients’ RF abilities to help them make sense of their symptoms and thus reduce them.